Aplicação da análise de modos e efeitos de falha (FMEA) para avaliação de situações de riscos no projeto de prevenção de incêndio da casa do estudante universitário (CEU-PR) - Ermenegildo, Ivo Marcelo (2014)
The Risk Management despite being often left out proves to be very important to the success of a project and the other project activities. Ignore it is to make the project vulnerable when an unexpected event occurs. Likewise, with the non-realization of risk management can ignore potential problems and miss the chance to fix them and keep them under control. This is the best way to measure and control the uncertainties. In this article, we tried to adjust the criteria of FMEA - Analysis of Failure Modes and Effects, based on preventing fires in an old building as CSCIP 2011. The methodology used was a qualitative survey through on-site observation and quantitative based on literature review of FMEA and CSCIP 2011, developing up a spreadsheet its relation probability / impact of the risks identified and classified in order of greatest risk as the severity, occurrence and detection.